2021
DOI: 10.1158/1078-0432.ccr-21-0748
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Platinum-free Interval and BRCA Reversion Mutations for Veliparib Monotherapy after Progression on Carboplatin/Paclitaxel for gBRCA Advanced Breast Cancer (BROCADE3 Crossover)

Abstract: AbbVie is committed to responsible data sharing regarding the clinical trials we sponsor. This includes access to anonymized, individual and trial-level data (analysis data sets), as well as other information (e.g., protocols and Clinical Study Reports), as long as the trials are not part of an ongoing or planned regulatory submission. This includes requests for clinical trial data for unlicensed products and indications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The gBRCA testing in TNBC/HER2-negative BC patients is potentially cost-effective The cost-effectiveness of the first-line use of PARPi or the universal testing in the general population of BC is not convincing [36][37][38][39][40][41][42]. Tuffaha et al reported the cost-effectiveness of the gBRCA testing established at the 10% pretest probability threshold [43]; hence expanding the gBRCA test from TNBC to all HER2-negative BC patients is potentially cost-effective, considering the high prevalence (~9.7%) of gBRCA mutations in HER2-negative BC patients.…”
Section: Primary Findingsmentioning
confidence: 99%
“…The gBRCA testing in TNBC/HER2-negative BC patients is potentially cost-effective The cost-effectiveness of the first-line use of PARPi or the universal testing in the general population of BC is not convincing [36][37][38][39][40][41][42]. Tuffaha et al reported the cost-effectiveness of the gBRCA testing established at the 10% pretest probability threshold [43]; hence expanding the gBRCA test from TNBC to all HER2-negative BC patients is potentially cost-effective, considering the high prevalence (~9.7%) of gBRCA mutations in HER2-negative BC patients.…”
Section: Primary Findingsmentioning
confidence: 99%
“…Studies have confirmed that low concentrations of taxane‐based drugs can upregulate the expression of BRCA1 in normal breast cells and breast cancer cells with low BRCA1 expression 6,7 . In a portion of clinical cases of taxane resistance, various pathways of acquired taxane resistance were activated, in which BRCA1 expression was found to be up‐regulated 8 . Regarding the mechanism of BRCA1 mutation leading to drug resistance of paclitaxel, we believe that it is related to homologous recombination (HR) pathway, which is a DNA repair mechanism in which BRCA proteins play a major role.…”
Section: Discussionmentioning
confidence: 93%
“…Among them, a platinum-free interval longer than 180 days was correlated with greater veliparib activity. 49 Regarding combination with immunotherapy, the TOPA-CIO phase II trial explored the safety and efficacy of niraparib in combination with pembrolizumab in patients with metastatic triple negative breast cancer (TNBC) including a cohort of patients with tumor BRCA1/2 mutation. 50 Among 15 patients with a tumor BRCA1/2 mutation, the objective response rate (ORR) was 47% and the median PFS was 8.3 months (95% CI, 2.1-not estimable).…”
Section: Practical Applicationsmentioning
confidence: 99%